2013
DOI: 10.1111/nph.12442
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of the C16 homoterpene TMTT in Lotus japonicus through overexpression of (E,E)‐geranyllinalool synthase attracts generalist and specialist predators in different manners

Abstract: SummaryPlant defenses against herbivores include the emission of specific blends of volatiles, which enable plants to attract natural enemies of herbivores.We characterized a plastidial terpene synthase gene, PlTPS2, from lima bean (Phaseolus lunatus). The recombinant PlTPS2 protein was multifunctional, producing linalool, (E)-nerolidol and (E,E)-geranyllinalool, precursors of (E,E)-4,8,12-trimethyltrideca-1,3,7,11-tetraene [TMTT].Transgenic Lotus japonicus and Nicotiana tabacum plants, expressing PlTPS2 or it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 41 publications
1
63
0
1
Order By: Relevance
“…For instance, carnivorous predatory mites (Phytoseiulus persimilis) preferred the odor source of lima bean (Phaseolus lunatus) plants attacked by spider mites (Tetranychus urticae) to the odor of plants damaged by beet armyworm (Spodoptera exigua) larvae (de Boer et al, 2004). TMTT might also play a role in indirect defense in floral tissues (Brillada et al, 2013). Still, the role of geranyllinalool in plant tissues is not well established.…”
Section: Nobilis a Dioecious Arboraceous Basal Dicotyledonous Spmentioning
confidence: 99%
“…For instance, carnivorous predatory mites (Phytoseiulus persimilis) preferred the odor source of lima bean (Phaseolus lunatus) plants attacked by spider mites (Tetranychus urticae) to the odor of plants damaged by beet armyworm (Spodoptera exigua) larvae (de Boer et al, 2004). TMTT might also play a role in indirect defense in floral tissues (Brillada et al, 2013). Still, the role of geranyllinalool in plant tissues is not well established.…”
Section: Nobilis a Dioecious Arboraceous Basal Dicotyledonous Spmentioning
confidence: 99%
“…This indicates that TPS2 is involved in the production of mono-, sesqui-, and diterpenes in planta. The closely related enzymes MtTPS3 from M. truncatula (Gomez et al, 2005;Arimura et al, 2008) and PlTPS2 from P. lunatus (Brillada et al, 2013) accept the same range of substrates in vitro, but their activities in the respective plant species have not been determined. The products of TPS2 have previously been identified as some of the major herbivore-induced volatiles of maize.…”
Section: The Terpene Synthase Tps2 Is Involved In Biosynthesis Of Botmentioning
confidence: 99%
“…These enzymes convert GGDP more efficiently than FDP in vitro and their transcript levels correlate with the formation of TMTT (SlGLS) and hydroxylinalool glycosides (NaGLS). Two geranyllinallool synthases from Fabaceae, PlTPS2 from P. lunatus (Brillada et al, 2013) and MtTPS3 from Medicago truncatula (Gomez et al, 2005;Arimura et al, 2008), belong to a separate clade of terpene synthases possibly involved in volatile terpene production. These enzymes are expressed in the plastid and convert GDP and FDP with higher in vitro efficiencies than GGDP.…”
Section: Introductionmentioning
confidence: 99%
“…7 The effects of TMTT and (E)-nerolidol as individual components or in blends have been studied mainly in predatory mites. 20,29 Coccinella septempunctata is an important predator of aphids, strongly attracted by volatiles of attacked plants, but knowledge of the role of these HIPV components on their behavior, alone or in blends, is lacking. It has been previously shown that ladybirds are attracted by changes in volatile profiles resulting from chemical interaction between unattacked barley plants 8,12,13 and the present study supports these findings and gives a potential explanation of the phenomenon.…”
mentioning
confidence: 99%